The use of hall’s technique preformed metal crown by paediatric dentists in Malaysia - Jesmin, Fabiha (2020)
Hall’s technique preformed metal crown (HTPMC) has been established as a novel method for managing decayed primary molars without local anaesthesia, caries removal and tooth preparation. Despite good evidence of its effectiveness, the usage of Hall’s technique among specialists and general dental practitioners are still noticeably low. Previously, no study has been carried out about Hall’s technique preformed metal crown in Malaysia. The expected outcome of this study will help to find out the practice rate and the barrier of practising HTPMC in Malaysia which could encourage the future dental practitioner for using HTPMC in their regular practice. The aim of the study is to assess the usage of Hall’s technique preformed metal crown among the paediatric dentists in Malaysia. This is a cross-sectional questionnairebased study among the paediatric dentists in Malaysia, and the questionnaire was distributed online to the paediatric dentists who are working in hospitals (MOH) and universities in Malaysia. Descriptive analysis was performed including percent distributions for demographic profile and questions related to HTPMC. SPSS modeler software was used to analysis the co-occurrence frequencies. The outcome of this study suggests a relatively high use of HTPMC. In this study, the response rate was 49% whereas only 32 paediatric specialists responded out of 65. Out of 32 paediatric dentists, 21 are (65.6%) using HTPMC in Malaysia. On the other hand, 66.7% (14) respondents always want to use HTPMC as a treatment option, 19% (4) as a treatment choice for a carious primary molar. On the other hand, 47.6% would prefer to use HTPMC in cavitated interproximal carious teeth, 19.0% in cavitated occlusal carious teeth. However, 23.8% (5) of them did not want to use HTPMC for non-cavitated occlusal carious teeth and only 9.5% (2) respondents who did not want to use it for non-cavitated interproximal carious teeth. Majority of the respondents would like to use HTPMC for special needs children 95.2% (20). However, they prefer to fit the metal crown under inhalation sedation 76.2%. Among all the perceived barriers of using HTPMC, 61.1% of respondents stated that they are unable to find the right size of the crown. About 60.0% of respondents are not using it because they do not like to fit the crown without removing caries completely. In conclusion, the usage of Hall’s technique preformed metal crown among the paediatric dentists in Malaysia is significantly high. According to the survey, most of the respondents would like to use HTPMC for special need children and more than half of them want to use under inhalation sedation. In addition, the working position of the respondent determined as the highest influencing factor of using HTPMC. Respondents who are lecturer, specialist and consultant using HTPMC for over 5 years. Moreover, respondents who completed their post-graduation from abroad are using HTPMC more frequently.